Queen Math - Lazebnaia A. V., Malykhina A. I. (Pedagogical excellence and pedagogical technologies, 2019)
This article describes the relevance of entertaining mathematics for the intellectual development of a child. A variety of didactic material contributes to the development of logical thinking, memory, attention, ingenuity.
Keywords: дидактический материал; интеллектуальное развитие; занимательная математика; урок математики; design; rebuses; analyze; labyrinths; charades; think logically